2021
DOI: 10.1515/jbcpp-2020-0310
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Ginkgo Biloba could use in the influenza and coronavirus COVID-19 infections

Abstract: Coronavirus COVID-19 pandemic invades the world. Public health evaluates the incidence of infections and death, which should be reduced and need desperately quarantines for infected individuals. This article review refers to the roles of Ginkgo Biloba to reduce the risk of infection in the respiratory tract, the details on the epidemiology of corona COVID-19 and influenza, and it highlights how the Ginko Biloba could have been used as a novel treatment. Ginkgo Biloba can reduce the risk of infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 132 publications
(155 reference statements)
1
17
0
Order By: Relevance
“…The Ginkgo biloba extract EGb 761 was beneficial in generalized anxiety disorder [177] and dementia [178], actions that may be useful for the neuropsychiatric aspects of long-COVID. Ginkgolic acid (GA) was shown to inhibit the fusion and synthesis of viral proteins [179]. Other studies have shown that green tea catechins could be useful in COVID-19 [180,181], especially against entry of SARS-CoV-2 [182].…”
Section: Discussionmentioning
confidence: 99%
“…The Ginkgo biloba extract EGb 761 was beneficial in generalized anxiety disorder [177] and dementia [178], actions that may be useful for the neuropsychiatric aspects of long-COVID. Ginkgolic acid (GA) was shown to inhibit the fusion and synthesis of viral proteins [179]. Other studies have shown that green tea catechins could be useful in COVID-19 [180,181], especially against entry of SARS-CoV-2 [182].…”
Section: Discussionmentioning
confidence: 99%
“…It seems essential to use this drug even prophylactically and not wait for the first signs of dementia in a diagnosed COVID-19 infection [ 118 ]. Anxiety and depression are equally dangerous ailments associated with COVID-19 virus infection, and it is imperative to treat them.…”
Section: Herbal Raw Materials That Inhibit Inflammation Of the Respir...mentioning
confidence: 99%
“…Ginkgo biloba contains quercetin, a polyphenol compound, and other components, and is suggested to have antiviral, antioxidant, anti-inflammatory, and immunomodulatory effects that decrease pro-inflammatory cytokines [ 85 ]. Ginkgo biloba contains two different groups of compounds: (1) flavonoid glycosides (rutin and quercetin) and (2) terpene lactones (ginkgolic acid and ginkgolides A–C) [ 86 ].…”
Section: Role Of Nutraceuticals/dietary Agents In Alleviating Neurolo...mentioning
confidence: 99%
“…A recent review by Ibrahim et al suggests that quercetin, a flavone extract of GB, can serve as an anti-inflammatory and immunomodulatory agent by the downregulation of many pro-inflammatory cytokines such as lipopolysaccharide (LPS)-induced tumor necrosis factor α (TNF-α), LPS-induced IL-8 in A549 cells in the lungs, and LPS-induced IL-1α and TNF-α in glial cells [ 85 ]. GA, an alkylphenol constituent of GB, has been shown to inhibit the viral protein-mediated host cell fusion in a variety of enveloped viruses (EBOV, HIV, ZIKA, HSV-1, HCMV, EBV, and IAV) and some non-enveloped viruses, which suggests that GA can potentially be used to treat other acute infections, including SARS-CoV-2 [ 85 , 87 ]. A recent study by Xiong et al also found that three ginkgo biloba leaf extracts (GBLEs)—GA C15:0, GA C17:1, and the bioflavone sciadopitysin—inhibit 3-Chymotrypsin-like protease (3CLpro), a virally encoded proteinase essential for the replication of SARS-CoV-2, in a reversible and mixed-inhibition manner [ 91 ].…”
Section: Role Of Nutraceuticals/dietary Agents In Alleviating Neurolo...mentioning
confidence: 99%